Internalisasi Nilai Susila dan Pendidikan Karakter Dalam Slokantara Untuk Penguatan Moderasi Beragama - Agus Gunada, I Wayan; Ratnaya, I Gede; Arta Wiguna, Ida Bagus Alit (Jurnal Penelitian Agama Hindu, 2023)
The aims of research to describe the sloka-sloka in Slokantara supporting the strengthening of character education, and character education are built as part of the harmonization of strengthening religious moderation. Religion is an attempt to build peace, but acts of intolerance and radicalism are denial and misappropriation of the essence of the religious process. This is important to reaffirm religious teachings, especially in the book of Slokantara, to strengthen character, support moderate religious behaviour, and build peace in Indonesia. This study uses qualitative research with a literature study approach and data analysis techniques in the form of document analysis of relevant libraries, especially the analysis of the Slokantara book. Based on the results of the interpretation of the book of Slokantara, it can be explained that there are values that are relevant and related to the concept of character education as formulated in national education. The moral values in it become a reinforcement to increase understanding of moderate behaviour for Hindus, to build harmonization between religious people. Character in the educational process is built on values, norms and morality, which are strengthened through the teachings contained in the scriptures. The study of ethical values in the book of Slokantara can be a foundation for strengthening character and aims to increase understanding of the importance of moderate behaviour to build a harmonious life between religious people. In addition, this study is expected to be a literature reference for relevant studies and research, especially studies on character education and religious moderation.